Creative Youth in a Changing Neighborhood: Public Policies, Projects and Associations in a Segregated Area in the Lisbon Periphery - Varela, Pedro; Raposo, Otávio; Ferro, L. (16th European Sociological Association Conference (ESA 2024), 2024)
Over the last months, we have been carrying out fieldwork in a neighbourhood on the outskirts of Lisbon that has undergone profound social changes. In the 1960s, this area was built as a housing project for fishermen's families. Then other buildings and temporary homes were constructed to rehouse people living in the nearby precarious self-built areas, many of them of Cape Verdean ancestry. Today it is a racially diverse community with white and Black residents, some Roma families, and others. While this neighbourhood was initially situated in an isolated area now nestled within one of the richest regions on the periphery of Lisbon and, in recent years, has garnered attention from local and state authorities. Today, the neighbourhood suffers from an intense gentrification process that prevents new generations from staying there. Despite having a reputation as a marginal and violent area, this community has seen a remarkable change both internally and in its image to the outside. With a strong dynamic of associations and projects (residents, youth, cultural, sports or welfare), this area has been a place where urban art and artistic practices have been promoted by young people through local public policies. We have been studying this dynamic and how local and state institutions influence their policies. Through ethnographic work as part of the Pericreativity project, this presentation aims to delve into the history and activity of neighbourhood projects and associations, understanding how they depend on or are autonomous about the public policies planned for this place.